Low digit ratio 2D:4D in alcohol dependent patients. - Johannes Kornhuber (Public Library of Science (PLoS), 2011)
The ratio of the lengths of the second and fourth finger (2D∶4D) has been described as reflecting the degree of prenatal androgen exposure in humans. 2D∶4D is smaller for males than females and is associated with traits such as left-handedness, physical aggression, attention-deficit-hyperactivity disorder and a genetic polymorphism of the androgen receptor. All of these traits are known to be correlated to the vulnerability for alcohol dependency. We therefore hypothesized low 2D∶4D in patients with alcohol dependency. In the present study on 131 patients suffering from alcohol dependency and 185 healthy volunteers, we found that alcohol dependent patients had smaller 2D∶4D ratios compared to controls with preserved sexual dimorphism but with reduced right-left differences. The detection of alcohol dependency based on 2D∶4D ratios was most accurate using the right hand of males (ROC-analysis: AUC 0.725, sensitivity 0.667, specificity 0.723). These findings provide novel insights into the role of prenatal androgen exposure in the development of alcohol dependency and for the use of 2D∶4D as a possible trait marker in identifying patients with alcohol dependency.